The value of mustard seed oil meal as a protein supplement for fattening pigs on alfalfa pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
Last year at the Livestock Feeders' Day, results of experiments were given on the use of mustard seed oil meal as a protein supplement for fattening pigs on alfalfa pasture. The results showed that mustard seed oil meal was an excellent protein feed when mixed with tankage and other protein supplements and self-fed free choice. Generally the gains were as cheap or cheaper than where tankage alone was fed and the daily gain were somewhat more rapid with a lower feed consumption. In the tests reported last year the mustard seed oil meal made up as much as 50 percent of the protein mixtures with tankage in some of the lots and at this level proved to be entirely palatable. The results of feeding it in such large proportions were so satisfactory that it was desired to ascertain whether it were possible to increase further the amount of mustard seed meal in the mixture with tankage and still get good results. Consequently two lots of pigs were fed this past summer with an increased percentage of the mustard seed oil meal.
Keywords: Swine; Mustard seed oil; Protein; Alfalfa pasture